1982
DOI: 10.1046/j.1468-2982.1982.0203145.x
|View full text |Cite
|
Sign up to set email alerts
|

Ergotamine in Plasma and CSF After i.m. and Rectal Administration to Humans

Abstract: An attempt was made to study the kinetics of penetration of ergotamine across the blood-brain barrier. A single therapeutic dose of ergotamine was given to 18 hospitalized patients; eight patients received 0.5 mg i.m., three patients 4 mg rectally, and seven patients 2 mg rectally. Plasma samples were drawn between 0.25 and 72 h and one CSF sample was taken from each patient between 0.5 and 6.5 h after administration. The ergotamine concentrations were measured using a RIA method. The 0.5 mg intramuscular inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…No other pharmacokinetic parameters were calculated from the plasma level data, though inspection of the plasma level-time curve published suggests an elim-ination half-life of about 3 h. The findings of these radio-immune assay studies suggest a substantially impaired bioavailability of the drug after oral and rectal administration. The differences in the CSF findings between Ala-Hurala et al (13) and Hovdal et al (15) are difficult to explain. The validity of some of the results is uncertain because much of the work was carried out near the limit of sensitivity of an assay which may not have distinguished between ergotamine, its isomer and its metabolites.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…No other pharmacokinetic parameters were calculated from the plasma level data, though inspection of the plasma level-time curve published suggests an elim-ination half-life of about 3 h. The findings of these radio-immune assay studies suggest a substantially impaired bioavailability of the drug after oral and rectal administration. The differences in the CSF findings between Ala-Hurala et al (13) and Hovdal et al (15) are difficult to explain. The validity of some of the results is uncertain because much of the work was carried out near the limit of sensitivity of an assay which may not have distinguished between ergotamine, its isomer and its metabolites.…”
mentioning
confidence: 83%
“…Hovdal et al (15) found a mean peak plasma ergotamine concentration of 1.27 ± S.E.M. 0.7 μg/ml 0.5 h after a 0.5 mg intramuscular injection of ergotamine tartrate, a mean plasma level of only 0.44 μg/ml with a broad peak between 0.75 and 2 h after a 4 mg rectal dosage and almost unmeasurable levels after a 2 mg rectal dosage.…”
mentioning
confidence: 98%
“…Since sumatriptan does not seem to penetrate the blood brain barrier (Dallas et al, 1989) and the evidence regarding penetration by ergotamine and dihydroergotamine is at best equivocal (in favour: Ala-Hurula et al, 1979;Goadsby & Gundlach, 1991;against: Eckert et al, 1978;Kanto et al, 1981;Hovdal et al, 1982), it would appear that the antimigraine effect of these drugs is related to a vascular effect, possibly involving a powerful vasoconstrictor activity on dilated and painful blood vessels. In addition, these drugs have been reported to inhibit extravasation of plasma in the dura mater following stimulation of the trigeminal ganglion in the rat Saito et al, 1988;Buzzi & Moskowitz, 1990); such an effect may also contribute to the antimigraine effect of these drugs.…”
Section: Possible Mechanisms In the Antimigraine Effectmentioning
confidence: 99%
“…Later the main component ergotamine was isolated from the mixture (1918) and was used for a long time in migraine therapy since 1926 [15]. Although a clear interaction of ergotamine with neurotransmitters is reported, the responsible mechanism is still controversial [16,17]. Peptide ergot alkaloids like ergotamine show a low oral bioavailability, less than 2% in humans [18].…”
Section: Introductionmentioning
confidence: 99%